Takhrij and Syarah Hadith of Agrotechnology The Study of Black Seed - Nandang Kusdinar; Wahyudin Darmalaksana; Muhammad Subandi (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad about Black Seed. This research method is qualitative through the approach of takhrij and sharah hadith with agrotechnolo analysis. The results and discussion of this research is about Black Seed, by analyzing its content, the benefits of Black Seed and various other benefits. The conclusion of this study is to inform that there are many benefits of Black Seed for body health.